2021
DOI: 10.31025/2611-4135/2021.14063
|View full text |Cite
|
Sign up to set email alerts
|

RECOVERY OF METALS FROM ELECTROACTIVE COMPONENTS OF SPENT Ni-MH BATTERIES AFTER LEACHING WITH FORMIC ACID

Abstract: this work describes a route for recovering nickel, cobalt, iron, zinc and lanthanides from spent nickel-metal hydride batteries. Formic acid was used as leachant. Experiments were run at 25-50°C for 1-4 h. Under the best conditions leaching yields surpassed 99 wt.%, except for iron. The insoluble matter contains almost solely iron as iron(III) basic formate. The leachate went through six separation procedures, combining solvent extraction with D2EHPA as extractant, and precipitation reactions. Fe2+ and Zn2+ we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…Halli et al [55] conducted an elution study using electric arc furnace dust and found up to 14% of Fe 2+ elution using 0.27 M formic acid in 168 h, which was a longer reaction time. Lower elution reactivity of Fe 2+ was also observed in other studies using formic acid as an extraction agent [56,57]. The Ca 2+ elution showed better results with maximum elution of 30% using 1.5 M solution at 12 min and 25 min steadily, followed by 23.6% using 1.0 M solution within 12 min, demonstrating a rapid initial rate of elution.…”
Section: Formic Acidsupporting
confidence: 78%
“…Halli et al [55] conducted an elution study using electric arc furnace dust and found up to 14% of Fe 2+ elution using 0.27 M formic acid in 168 h, which was a longer reaction time. Lower elution reactivity of Fe 2+ was also observed in other studies using formic acid as an extraction agent [56,57]. The Ca 2+ elution showed better results with maximum elution of 30% using 1.5 M solution at 12 min and 25 min steadily, followed by 23.6% using 1.0 M solution within 12 min, demonstrating a rapid initial rate of elution.…”
Section: Formic Acidsupporting
confidence: 78%